IMO-COMPLIANT ANALYSIS OF THE LARGE ANGLE STABILITY OF CHEMICAL TANKERS DURING THE LOADING AND UNLOADING LIQUID CAUSTIC SODA - Firdhaus, Ahmad; Pujo, Mulyatno Imam; Luqman, Hakim Muhammad; Sekar, Wangi Nimas Ayu (Jurnal Rekayasa Mesin, 2023)
MT. Sinar Masela 8831 DWT is a ship transporting oil and chemicals certified by IMO Chemical Class 2,3. According to Chapter B, SOLAS CHAPTER VII, regarding water safety, loading and unloading oil and chemicals is categorized as dangerous due to water damage and pollution. Various studies are needed to expedite the loading and unloading process to reduce damage and pollution in the waters. One of these studies is regarding the stability of ships in accordance with IMO criteria. The study was conducted to determine the ship stability on the MT. Sinar Masela is in the loading-unloading process. This study applies eight conditions with seven-compartment tanks on the ship using software to analyze the stability calculation when the loading-unloading process meets the stability criteria set by IMO A.749(18) Ch 3. The results show the measure of stability in eight conditions with a seven-compartment tank during the loading and unloading process has a higher GZ value in all states, which has met the IMO stability criteria. Comparison of stability calculations on loading and unloading has an average difference of 0.226 m at 2.075 deg at the GZ value in each condition.